2019
DOI: 10.3389/fgene.2018.00692
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to Improve Resilience in Animal Breeding Programs

Abstract: Resilience is the capacity of an animal to be minimally affected by disturbances or to rapidly return to the state pertained before exposure to a disturbance. However, indicators for general resilience to environmental disturbances have not yet been defined, and perhaps therefore resilience is not yet included in breeding goals. The current developments on big data collection give opportunities to determine new resilience indicators based on longitudinal data, which can aid to incorporate resilience in animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
365
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(373 citation statements)
references
References 59 publications
8
365
0
Order By: Relevance
“…Similarly, Bryant et al (2006) suggested the development of customized EBV for specific environments, and (Nguyen et al, 2017) proposed a selection tool that could balance the profit index and heat tolerance. More recently, some authors have demonstrated opportunities for including resilience in breeding goals (Mulder, 2016;Friggens et al, 2017;Berghof et al, 2019). Berghof et al (2019) proposed using the slope of the reaction norms as an indicator trait for resilience to heat stress and calculating economic values for selection index based on the reduced labor costs associated with the management of heat-stressed animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Bryant et al (2006) suggested the development of customized EBV for specific environments, and (Nguyen et al, 2017) proposed a selection tool that could balance the profit index and heat tolerance. More recently, some authors have demonstrated opportunities for including resilience in breeding goals (Mulder, 2016;Friggens et al, 2017;Berghof et al, 2019). Berghof et al (2019) proposed using the slope of the reaction norms as an indicator trait for resilience to heat stress and calculating economic values for selection index based on the reduced labor costs associated with the management of heat-stressed animals.…”
Section: Discussionmentioning
confidence: 99%
“…Resilient animals are minimally affected by environmental disturbances (Colditz and Hine, 2016;Berghof et al, 2019), and their performances are expected to be comparatively consistent under different heat stress conditions. Our results suggest that the proportion of resilient sires has decreased in recent years (Figure 8), confirming the increasing relevance of G × E in the study population.…”
Section: Quantifying Resilience To Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to identify which of the three periods better expressed the impact of FT on performance, two additional analyses were performed. First, the residual variance () of the data for each of the window periods were estimated with the model below, in order to identify the period in which greater variability of the data was observed, which is an indication of response to diseases [23]: where AWG ijk , μ , L i , p j , b 1 , iBW k , and e ijk are as previously defined in Eq. 1.…”
Section: Methodsmentioning
confidence: 99%
“…The h 2 v,litter can be interpreted as the reliability of EBVs based on a single litter. More recently, Berghof et al (2019) proposed the heritability of the residual variance for repeated records: ) and r records is the repeatability of the residual variance. Berghof et al (2019) show that reasonable heritabilities of 0.2 can be obtained at the animal level when having at least 50 observations, which is in agreement with recent empirical studies by Putz et al (2018) and Poppe et al (in press).…”
Section: Associated With Residual Variancementioning
confidence: 99%